Chinese Exceptionalism? Folk Religions and Subjective Well-being - Luo, Lang (Review of religious research, 2024)
Folk religions are reviving in contemporary China. They are distinctive from institutionalized religions and share many qualities with the emerging religious phenomena in the West. Despite their significance, however, the lack of concise frameworks and causal analysis methods has hindered a deeper understanding of these religions. By integrating psychological and sociocultural perspectives, this study concentrates on subjective well-being and tailors a micro model applicable to analyzing Chinese folk religions, along with a novel instrumental variable for causal identification. Empirical evidence suggests that folk religions have negative effects on subjective well-being, resulting in a 17.3 percent decrease in subjective well-being compared to the sample mean. This is primarily due to believers seeing folk religions as mere means for achieving earthly targets, therefore suffering from strengthened negative senses and motivated radical behaviors. Nevertheless, investing in folk religions to a high degree might transform believers’ attitudes from seeing folk religions as means to seeing them as ends, thereby alleviating the negativity. This alleviation is mainly derived from positive senses, self-regulation, and inclusive attitudes towards society. Hence, taking religions more seriously and not utilitarianly, or fulfilling unmet targets more effectively, are two paths to eliminate the negative effects.